How Second Language Learning Reshapes the Brain: A Narrative Review of Neurolinguistic Evidence (Al-Farooq Journal of Sciences, 2026)
Second language (L2) learning is a complicated process that can lead to significant changes in the brain’s function and structure. This research paper examines neurolinguistic evidence on how learning a second language reshapes the brain and identifies the major factors that influence language-related neuroplasticity. Drawing on findings from neuroimaging and cognitive neuroscience research, this review explores both structural and functional brain changes associated with second language learning; changes in grey matter, white matter connectivity, cortical organization, and neural efficiency are included. In addition, it explores the influence of age of acquisition, language proficiency, exposure, immersion, learning intensity, and individual differences as well. The review also discusses the cognitive benefits of bilingualism, particularly in executive functions, attention, working memory, and cognitive flexibility. It considers the implications of neurolinguistic evidence for English language teaching, emphasizing retrieval practice, spaced repetition, multimodal learning, meaningful interaction, feedback, and sustained exposure. The evidence suggests that L2 learning is a dynamic experience which can enhance lifelong neuroplasticity and cognitive adaptation, while also providing valuable insights for developing more effective, brain-informed language teaching practices.
Keywords: neurolinguistics; neuroplasticity; second language acquisition; bilingualism; brain and language; executive functions; English Language Teaching